Variability and stability of essential oil composition in Ukrainian hop varieties - Protsenko, Lidia; Janse, Liliya; Koshytska, Nina; Ryzhuk, Serhii; Liashenko, Mykola; Bober, Anatolii; Gunko , Sergiy (KVASNY PRUMYSL, 2023)
The aim of the study was to evaluate the variation in essential oil content and composition within nine distinct Ukrainian hop varieties, with a particular focus on their genetic stability and suitability for brewing applications over 11 years of their cultivation. The hydrodistillation method (Analytica-EBC 7.10) was used to evaluate hop essential oil content and gas-liquid capillary chromatography (Analytica-EBC 7.12) to discern its qualitative composition. Variability was evaluated using statistical parameters. The essential oil content across the studied varieties spanned from 0.51 to 2.58 ml/100 g of dry hop cones. The highest content was measured in the bitter-aroma variety with a special aroma – Ruslan. The predominant essential oil components, including myrcene, caryophyllene, humulene, and farnesene, collectively constituted 70.0–84.2% of the total amount. The aroma varieties displayed myrcene content typical for European varieties (with the level up to 56.2% in the Ruslan variety). Farnesene content exhibited significant variation ranging from 0.3 to 17.6% with the highest content in Saaz-type varieties (Klon 18, Zlato Polissya, and National) and the bitter type Promin variety. Humulene content ranged from 13.2 to 32.6%. Among all studied varieties, Alta displayed the least variability for all parameters evaluated (Cv = 15.2%). This study underscores the genetic basis of essential oil composition in hops, emphasizing its potential as a biochemical criterion for identifying hop breeding varieties. The study revealed, that despite annual fluctuations, the essential oil content and composition remained within passport data declared for the variety. The findings provide valuable insight into a sustainable cultivation and optimal utilization of hops in the brewing industry.